Accuracy and Reproducibility of High-definition Anorectal Manometry and Pressure Topography Analyses in Healthy Subjects - Coss-Adame, Enrique; Rao, Satish S.C.; Valestin, Jessica; Ali-Azamar, Amyra; Remes-Troche, Jose M. (Clinical gastroenterology and hepatology, 2015)
High-definition anorectal manometry (HDAM-3D) provides a topographic and 3-dimensional profile of anorectal pressure. We assessed anorectal sensorimotor function and the reproducibility of measurements made with HDAM-3D in healthy adults, and the accuracy of data analysis by its software. Anal sphincter pressures and rectal sensory thresholds were measured in 78 healthy subjects via placement of a 10-mm rigid probe, with 256 circumferentially arrayed pressure sensors, and a balloon in the rectum. The bearing down maneuver was assessed in a subset of 18 subjects. We compared data analyzed by an expert with findings from automated software analysis. Measurements made in a subset of 16 subjects, 2 weeks apart, were compared to determine reproducibility. Resting, squeezing, and sustained squeezing pressures were significantly higher in men than in women (P < .05); other parameters were similar. Desire and urgency to defecate were similar between men and women, but the maximal tolerable volume was significantly lower in women (P < .05). Older women (>50 years) had significantly lower resting (P < .01) and sustained squeeze pressures (P < .04). Dyssynergic patterns of defecation were observed in 12 of 18 subjects (67%) who attempted to defecate without the 60-mL rectal balloon distention and in 6 of 18 subjects (33%) with the 60-mL rectal balloon distention. Test-retest values correlated (r = 0.81), as did analyses made by an expert vs software analyses of data (r = 0.99). On the basis of HDAM-3D measurements in healthy adults, anal sphincter pressures are higher in men than in women, but sensory and other parameters are similar; older subjects have weaker sphincters. Many people were found to have dyssynergic patterns of defecation, which could be related to the probe or other technical issues, so this technique may not be suitable for assessing defecation patterns. Measurements made by HDAM-3D are reproducible, and data can be accurately analyzed by its software.